Analyzing and comparing the technical performance of the Iraqi national team players on wheelchairs participating in the Arab Basketball Championship 2016 - Kareem, OdayAbdulhussein (International Journal of Psychosocial Rehabilitation, 2020)
Disabled sport is one of the most important special sports at the present time because of its great role in rehabilitating the disabled to achieve high sporting achievements and raise the name of their countries in international forums. Because he has players who have good physical and skill abilities that play a major role in achieving positive results for their country, and because the researcher is one of the referees accredited to the Iraqi Basketball Federation as well as the West Asian Federation on wheelchairs and participated in leading the West Asian Championship matches as well as the Arab Championship, he noticed there is a discrepancy in The technical level of the Iraqi team players varied from one tournament to another, and here lies the problem of the research, so he wanted to stand on the technical level for them in the Arab tournament, as well as compare them with some of the participating tournament teams, as the research aimed to identify the technical level for some teams participating in the Arab Championship, as well as a comparison in the technical level of the Iraqi team with some of the technical level of some of the participating teams. The researcher concluded that there were positive results for the Iraqi team through the analysis in shooting from the free throw during the two matches of Morocco and Algeria, and the researcher recommended working on developing skill capabilities for Iraqi basketball players on wheelchairs.